(untitled) (Texas Journal of Agriculture and Biological Sciences, 2026)
Verbena officinalis L. perennial herbaceous plant of the Verbenaceae family and a cultivated flower of the subshrub family. Its homeland is Peru. More than 200 species grow in the tropical and subtropical regions of the Americas. The flowers are corymbose, in a raceme 6-7 cm in diameter, white, red, pink, yellow, or purple. It is cold-resistant and does not freeze even under early snowfall. Verbena is propagated by seed. Seeds are sown in greenhouses in February and March. It flowers from June to October. The stem is erect and branched. The essential oil contained in the leaves and inflorescences is also used in perfumery